Early mobilisation in Windhoek intensive care units: Practices, attitudes and barriers - Ilse du Plessis; Savarna Francis; Brenda Morrow (South African Journal of Physiotherapy)
Background: Early mobilisation (EM) of critically ill patients in intensive care units (ICUs) has gained significant attention because of its potential to improve patient outcomes. Despite the recognised benefits of EM, implementation remains inconsistent.